Development of Electromagnetic Picking System for Weaving Loom - Kamalaruban, K.; Hamsathvanie, K.; Selvalojini, S.; Thiruvaran, T.; Arunan, S. (My University, 2015)
In the weaving industry, the picking speed is the key factor which determines the production rate. There are various types of modern picking systems available in weaving industry such as air jet, water jet, and projectile picking systems. However, the developments of cheaper and high speed picking mechanism still has been a huge challenge in the textile industry. The present study describes the electromagnetic picking system which can be portable and simply integrated with conventional shuttle weaving looms to increase the picking speed with low cost.
Keywords: Electromagnetism; Solenoid